Awareness and experience of mindfulness in Britain - Simonsson, O; Fisher, S; Martin, M (SAGE Publications, 2020)
In recent years, the practice of mindfulness has become increasingly popular, but there is very little evidence on how many and what kind of people have heard of and learnt to practise mindfulness. Using data from an online survey on a sample of 1013 adults in Britain in November 2018, this study aims to estimate the prevalence of mindfulness use among adults in Britain and to identify the sociodemographic and political characteristics associated with awareness and experience of mindfulness. The findings suggest that 15% of adults in Britain had learnt to practise mindfulness, which is significantly more than the finding that 2.5% of adults in the United States in 2012 had practised mindfulness in their lifetime. Although widespread, awareness of mindfulness was more common among women, unmarried adults, adults from middle and high-income households, and those who voted Remain in the 2016 Brexit Referendum. Higher levels of engagement with mindfulness, beyond awareness, were more likely among young and middle-aged adults, but otherwise not concentrated in any particular groups.